That My Neighbor's Cow Might Live: Effectuation and Entrepreneurship Education in Croatia - Harmeling, Susan (Senate Hall, 2008)
Post-war Croatia has been characterized by high unemployment, a damaged infrastructure, stalled foreign investment and few government incentives for new business creation. It is in this context that a prominent local professor in Osijek, in the eastern part of the country, started a unique MBA program focused on entrepreneurship. The aim of the program was to give hope to some of the region's young people after years of struggle and lost time during the Balkan Wars.This paper provides an analysis of how the program came into existence by examining both the unique Croatian context and the process of effectuation. Because it highlights both of these aspects of the story - context and process - the model may serve as an example for the creation of other, similar initiatives in areas where economic development is sorely needed, and where entrepreneurship education may represent one way to boost regional economies.
Keywords: entrepreneurship education|effectuation|economic development